2023
DOI: 10.7189/jogh.13.06026
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of clinical signs and symptoms of COVID-19: A systematic review and meta-analysis to investigate the different estimates in a different stage of the pandemic outbreak

Abstract: Background The coronavirus (COVID-19) pandemic caused enormous adverse socioeconomic impacts worldwide. Evidence suggests that the diagnostic accuracy of clinical features of COVID-19 may vary among different populations. Methods We conducted a systematic review and meta-analysis of studies from PubMed, Embase, Cochrane Library, Google Scholar, and the WHO Global Health Library for studies evaluating the accuracy of clinical features to predict and prognosticate COVID-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 59 publications
(66 reference statements)
0
1
0
Order By: Relevance
“…Tons of studies and research in a myriad of different settings have demonstrated the dramatic impact of the new severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2)‐induced disease (COVID‐19) with its subsequent variants toward human beings both in terms of acute safety issues and long‐term sequelae 1–6 . This has been certainly true and hugely sensitive mostly in unvaccinated individuals 7–10 .…”
Section: Introductionmentioning
confidence: 99%
“…Tons of studies and research in a myriad of different settings have demonstrated the dramatic impact of the new severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2)‐induced disease (COVID‐19) with its subsequent variants toward human beings both in terms of acute safety issues and long‐term sequelae 1–6 . This has been certainly true and hugely sensitive mostly in unvaccinated individuals 7–10 .…”
Section: Introductionmentioning
confidence: 99%